ON THE PATH TO TOURISM DIGITALIZATION: THE DIGITAL ECOSYSTEM BY THE EXAMPLE OF KAZAKHSTAN - Balzhan SHILIBEKOVA; Roman PLOKHIKH; Lóránt Dénes DÁVID (Geo Journal of Tourism and Geosites)
Global digitalization dramatically affects tourism actions, varying the principles of its organization, data support and the traveler himself. The main goal of the study is to analyze the digitalization process of the tourism industry at the current stage of development and its state in Kazakhstan. The article considers the issues related to the impact of electronic technology on the growth and progress of digitalization in tourism. An overview of examples for the tourism digital technologies is provided. Crucial new trends in the industry of tourism associated to digitalization are identified. The conducted research on the application of several scientific methods and technologies of information processing was based. In particular: bibliometric analysis in the field of tourism digitalization and digital ecosystems; study of Kazakhstan’ tourist Internet portals; survey of representatives of Kazakhstan’ travel agencies and modeling based on regression ordinal model. Bibliometric analysis was used to study the success level implementation of the activities in the field of tourism digitalization. This method was as a basis for identifying gaps, formed and future trends in the field of digital tourism ecosystem. The data source was the databases, which includes a wide range of publications on tourism scientific issues. The main analysis of articles was carrie d out in the special software Voyant Tools. Two additional research methods in this paper are applied: content analysis and modeling based on regression ordinal model. The current state of the market place in tourism, the level of application of elements of digital technologies in the sphere of tourism based on Kazakhstan' tourist platphorms is evaluated. With the help of a survey it was analyzed the degree of penetration of digital technologies currently used by companies in the local tourism market.